Impact of Sprouting Process on the Protein Quality of Yellow and Red Quinoa (Chenopodium quinoa) - Hassan Barakat; Maryam M. Al-Qabba; Raya Algonaiman; Khadija S. Radhi; Abdulkarim S. Almutairi; Muath M. Al Zhrani; Ahmed Mohamed (Molecules, 2024)
The demand for plant-based proteins has increased remarkably over the last decade. Expanding the availability and variety of plant-based protein options has shown positive potential. This study aimed to investigate the qualitative and quantitative changes in amino acids of yellow and red quinoa seeds (YQ and RQ) during a 9-day germination period. The results showed that the germination process led to an increase in the total amino acids by 7.43% and 14.36% in the YQ and RQ, respectively. Both varieties exhibited significant (p < 0.05) increases in non-essential and essential amino acids, including lysine, phenylalanine, threonine, and tyrosine. The content of non-essential amino acids nearly reached the standard values found in chicken eggs. These results were likely attributed to the impact of the germination process in increasing enzymes activity and decreasing anti-nutrient content (e.g., saponins). A linear relationship between increased seeds’ hydration and decreased saponins content was observed, indicating the effect of water absorption in changing the chemical composition of the plant. Both sprouts showed positive germination progression; however, the sprouted RQ showed a higher germination rate than the YQ (57.67% vs. 43.33%, respectively). Overall, this study demonstrates that germination is a promising technique for enhancing the nutritional value of quinoa seeds, delivering sprouted quinoa seeds as a highly recommended source of high-protein grains with notable functional properties.